Ideational Metaphor in English and Vietnamese Behavioral Clauses - Tu Trinh, Nguyen Thi; Van Hoa, Phan; Huu Phuc, Tran (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The concepts of ideational and interpersonal metaphor are introduced in Halliday’s An Introduction into Functional Grammar (1985) in which he differentiates his newly-identified grammatical metaphor from “figures of speech” metaphor. This article is devoted to interpreting the three major types of typical patterns of the ideational grammar of behavioral clauses in English and Vietnamese within the framework elaborated by Halliday and Matthiessen (2000, 2004); Martin et al. (1997) as well as making comparisons of these patterns in the two languages. Attention has been paid to describing a wide range of constructions and shift patterns of ideational metaphor (transitivity metaphor) and the grammatical variants between congruent and incongruent forms applying to transitivity configurations in English and Vietnamese behavioral clauses. The analysis of characteristics of ideational metaphor in behavioral clauses is conducted on five English and five Vietnamese novels and short stories from the 19th century to present. The conclusion points out some new results and suggests some practical applications.Received 3rd November 2017; Revised 27th March 2018; Accepted 30th April 2018